Rongga mulut mempengaruhi pola spektrum frekuensi suara pada penerapan klinis pengucapankataBahasa Indonesia:Pada anaklaki-laki usia 9 dan12tahun dengan maloklusi klas I Angle variasi berjejal (Oral cavity affect spectrum pattern ofvoice frequencyonclinicalimplementation of pronuncingwords in BahasaIndonesia : On 9 and 12-year-old boys in Angle Class I malocclusion with crowding variation) - Rinaldi Budi Utomo (Journal of Dentomaxillofacial Science, 2015)
The aim of this study was to determine the effect of cavum oris to spectrum pattern of voice frequency on the clinicalimplementation of pronouncing 7 words in a list of Indonesian words by 9 and 12 year-old children in Angle Class Imalocclusion with crowding variation. Analytical epidemiologic study with cross sectional design was performed in onetime measurement on the subject. The research subjects were 24 Javanese boys, who used standard and correct BahasaIndonesia. They were divided into two age-based groups: 12 children of 9 years old and 12 children of 12 years old. Thesetwo groups pronounced the seven words in the list which have frequency in their dominant sounds on Angle class Imalocclusion with crowding variation. They are /produktif/, /mushola/, /rupiah/, /identifikasi/, /yodium/, /hinggap/, and/hujan/. The sound was directly recorded in sound-proof room employing sound recorder program, flat microphone and sound processing mixer. Then the dominant sound frequency was measuredtogether with spectrum patterns of voicefrequency display by usingCoolEdit Pro 2.0andExcel software. Theresults showedcavumoris volume of 9-year-old malechildren is smaller than that of 12-year-old children. The spectrum pattern of voice frequency of the 7 words showed thatthe pattern and frequency chart equations of the 9 year-olds are of a lower amplitude and thinner pattern than those ofthe 12-year olds.